High-level competition, an essential benchmark for establishing the means of training Olympic-level female wrestlers - Grigore, E.-A.; Talaghir, L.-G.; Moisescu, P.; Grigore, A. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2025)
High-level competition, an essential benchmark for establishing the means of training Olympic-level female wrestlers. This paper presents a research study focused on the in-depth analysis of high-level competition in women's wrestling, aiming to identify and systematize the latest trends observed during contests and direct combat situations. Understanding these competitive dynamics is essential for designing optimized training programs for Olympic-level performance.The study investigates the key technical-tactical, physical, and physiological characteristics that define elite-level competition. By analyzing official match recordings and performance data from international tournaments, including the Olympic Games and World Championships, we identified a range of indicators that offer valuable insights into the demands placed on athletes at the highest level. Among the variables taken into consideration were the total duration of the contest, the effective active time during direct confrontation, the average number of matches required to win medals, as well as a series of specific technical-tactical elements. These include the frequency and type of scoring actions, transition moments, defensive and offensive strategies, and recovery intervals within a match. The technical-tactical analysis was conducted both at a general level and individually, by weight category. Particular attention was paid to the diversity of techniques used, the tempo of the fight, and the strategic differences between lightweight, middleweight, and heavyweight athletes. The individual characteristics of each athlete, especially those determined by the specific requirements of each weight class, reveal significant differences in the way technical-tactical expression manifests both quantitatively and qualitatively during matches. The findings provide a comprehensive and structured reference framework that can be used to guide the development of evidence-based training methods tailored to the realities of modern female wrestling at the Olympic level.